Role of Lipid Peroxidation and PPAR-δ in Amplifying Glucose-Stimulated Insulin Secretion - Cohen, Guy (American Diabetes Association, 2011)
OBJECTIVE: Previous studies show that polyunsaturated fatty acids (PUFAs) increase the insulin secretory capacity of pancreatic β-cells. We aimed at identifying PUFA-derived mediators and their cellular targets that are involved in the amplification of insulin release from β-cells preexposed to high glucose levels. RESEARCH DESIGN AND METHODS: The content of fatty acids in phospholipids of INS-1E β-cells was determined by lipidomics analysis. High-performance liquid chromatography was used to identify peroxidation products in β-cell cultures. Static and dynamic glucose-stimulated insulin secretion (GSIS) assays were performed on isolated rat islets and/or INS-1E cells. The function of peroxisome proliferator–activated receptor-δ (PPAR-δ) in regulating insulin secretion was investigated using pharmacological agents and gene expression manipulations. RESULTS: High glucose activated cPLA(2) and, subsequently, the hydrolysis of arachidonic and linoleic acid (AA and LA, respectively) from phospholipids in INS-1E cells. Glucose also increased the level of reactive oxygen species, which promoted the peroxidation of these PUFAs to generate 4-hydroxy-2E-nonenal (4-HNE). The latter mimicked the GSIS-amplifying effect of high glucose preexposure and of the PPAR-δ agonist GW501516 in INS-1E cells and isolated rat islets. These effects were blocked with GSK0660, a selective PPAR-δ antagonist, and the antioxidant N-acetylcysteine or by silencing PPAR-δ expression. High glucose, 4-HNE, and GW501516 also induced luciferase expression in a PPAR-δ–mediated transactivation assay. Cytotoxic effects of 4-HNE were observed only above the physiologically effective concentration range. CONCLUSIONS: Elevated glucose levels augment the release of AA and LA from phospholipids and their peroxidation to 4-HNE in β-cells. This molecule is an endogenous ligand for PPAR-δ, which amplifies insulin secretion in β-cells.